2016
DOI: 10.1177/1098612x16660356
|View full text |Cite
|
Sign up to set email alerts
|

Middle ear polyps: results of traction avulsion after a lateral approach to the ear canal in 62 cats (2004–2014)

Abstract: Objectives The objective of this study was to report the surgical outcome and complication rate of deep traction avulsion (TA) of feline aural inflammatory polyps after a lateral approach (LA) to the ear canal. Methods This was a retrospective analysis of data retrieved from an electronic database of 62 cats treated with TA after an LA (TALA) for removal of ear canal polyps. Long-term outcome was assessed via a telephone questionnaire survey with the owners. Results Domestic shorthair cats (48%) and Maine Coon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…More cats had recurrence of aural IP with simple traction (traction performed without curettage of the tympanic cavity) removal versus surgical intervention, a finding consistent with comparisons from previous reports. [19][20][21][22][23] For those cats where recurrence was documented, use of topical and/or systemic glucocorticoids did not seem to have an impact on time to recurrence. A larger sample size may have yielded different results, as several authors 23 have suggested a relationship between glucocorticoid therapy and lack of recurrence of polyps.…”
Section: Discussionmentioning
confidence: 99%
“…More cats had recurrence of aural IP with simple traction (traction performed without curettage of the tympanic cavity) removal versus surgical intervention, a finding consistent with comparisons from previous reports. [19][20][21][22][23] For those cats where recurrence was documented, use of topical and/or systemic glucocorticoids did not seem to have an impact on time to recurrence. A larger sample size may have yielded different results, as several authors 23 have suggested a relationship between glucocorticoid therapy and lack of recurrence of polyps.…”
Section: Discussionmentioning
confidence: 99%
“…2 This association is further supported by frequent reports of Horner syndrome occurring postoperatively following polyp removal using traction avulsion or ventral bulla osteotomy. 5557…”
Section: Discussionmentioning
confidence: 99%
“…66 In addition to signs of otitis externa, affected patients may have vestibular signs, respiratory signs, ocular discharge or blepharo spasm, or Horner's syndrome. 66,68 IAPs occur most commonly in young cats and kittens, though they can develop at any age. 66,68,69 If visible on otoscopy, IAPs often appear as a smooth, pink nodule in the canal at the level of the tympanum (Figure 4).…”
Section: O N T R I B U T I N G F a C T O R S T O F E L I N E O T I T I Smentioning
confidence: 99%
“…65 IAPs are usually treated in one of two ways: traction avulsion or ventral bulla osteotomy (VBO). 66,68 At the time of the procedure, cats should be evaluated for concurrent nasopharyngeal polyp. 65 Complications may occur with either of these treatment approaches, including Horner's syndrome, vestibular signs, hemorrhage and facial nerve paralysis.…”
Section: O N T R I B U T I N G F a C T O R S T O F E L I N E O T I T I Smentioning
confidence: 99%
See 1 more Smart Citation